Psychological ownership and knowledge sharing: Key psychological drivers of sustainable tourist behavior - Nguyen, Tho Huu-Hoang; Nguyen, Giang Thuy; Tučková, Zuzana; Hoang, Sinh Duc (Acta psychologica, 2025)
As the green transformation sweeps across industries in the digital age, tourism stakeholders face a pressing need to utilize online platforms and digital influencers for sustainability messaging. Drawing on the Motivation-Opportunity-Ability framework, this study investigates the influence of green ownership psychology and green knowledge sharing on tourists' repatronage intentions. It focuses on the mediating role of cooperative green activity programs and the moderating impact of tourists' green trust in social media influencers. Results from a two-wave survey of 602 tourists in Vietnam show that green practices directly increase repatronage intentions. Cooperative green activity programs significantly mediate this relationship, enhancing the impact of green marketing practices on repatronage intentions. Furthermore, tourists' green trust in social media influencers is a crucial moderating factor. It increases the effectiveness of green ownership psychology and green knowledge sharing in influencing repatronage intentions through cooperative green activity programs. The study highlights how the emotional and cognitive aspects of green marketing contribute to tourists' decisions to revisit or continue using tourism services. Offering original insights into the interplay of these elements in green marketing within the tourism industry, this research enriches the application of the Motivation-Opportunity-Ability framework. It provides valuable implications for tourism companies aiming to foster sustainable practices and enhance customer loyalty, highlighting the role of digital influencer engagement and cooperative sustainability initiatives in green marketing strategies.
Keywords: Motivation-Opportunity-Ability; marketing; Social Media; mužské pohlaví; Ownership; Male; turistika; Female; Humans; tourists' repatronage intentions; motivace; lidé; Green knowledge sharing; tourists' green trust in social media influencers; Middle Aged; ženské pohlaví; lidé středního věku; Tourism; Green ownership psychology; Motivation; Young Adult; mladý dospělý; Vietnam; Marketing; dospělí; Adult; úmysl; vlastnictví; sociální média; Intention; Cooperative green activity programs